Correlation of numeric rating scale with pure tone audiogram for assessing hearing loss (Bangladesh Journal of Medical Science, 2013)
Objective: Hearing loss is the public health problem affecting all the age groups. For the assessment of hearing loss pure tone audiogram (PTA) is the gold standard but cannot be easily available in rural areas. So, the main aim of our study is to see the correlation of numeric rating scale with the pure tone audiogram for assessing the hearing loss. Materials and methods: This was the prospective, non randomized and longitudinal study performed in two hundred patients with unilateral hearing loss. For the study purpose, the numeric rating scale (NRS) was divided into 5 parts as that of degree of hearing loss and the PTA was also divided into 5 parts to see the correlation with the NRS findings. The analysis was done using SPSS 16.0 Software. Results: The total frequency of unilateral hearing loss was 1.79%. 125(62.5%) patients fell within 16 25years.The mean age was 23.2+/-9.7. Females were affected more than males. Most of the patients who were in high school had unilateral hearing loss. Students and housewives accounted for 87.5%. 89% patients had conductive hearing loss, 10% had sensorineural hearing loss whereas only 1% patients had mixed hearing loss. The most of patients reported NRS2 and NRS3 which was 85.5%. Regarding the PTA analysis, 91% patients fell within mild and moderate hearing loss. There was high degree of correspondence in mild hearing loss between NRS and PTA. The Pearsons correlation showed the statistically significant correlation between NRS and PTA with p=0.00 Conclusion: The NRS scale can be used as an optional measure for PTA in assessing the hearing loss mainly in rural areas for screening where there is lack of PTA. DOI: http://dx.doi.org/10.3329/bjms.v13i1.13285 Bangladesh Journal of Medical Science Vol. 13 No. 01 January 2014: 25-29